Perancangan Strategi Pemasaran pada Coffee Shop dengan Metode SWOT dan QSPM: Studi Kasus: Kafe Ruang Warga - Febriansyah, Akbar Sodikin (Sci-tech Journal, 2024)
Marketing strategies in cafés are essential to attract and retain customers. This can be done through the use of social media and influencers, as well as ensuring product quality, service, and speed. Ruang Warga is a café in Jombang district. The implementation of inappropriate marketing strategies during the pandemic has made it difficult for Ruang Warga café to survive in today's business competition. Judging from January to May, visitor data is not stable and has even decreased with 1731 visitors in February. The purpose of this study is to implement a product marketing strategy using the SWOT and QSPM methods. This research uses SWOT and QSPM methods which are useful for knowing internal and external factors that can affect product sales. Then with the proposed improvements to increase consumer attractiveness to face market competition. The results of the SWOT analysis obtained three alternative strategies with the QSPM matrix to determine the strategic priority ranking. With the results of TAS 6.81, namely by prioritizing and developing marketing through social media by reaching a wider target market and making it easier to increase cafe branding. By prioritizing and developing marketing through social media, it can reach a wider target market and make it easier to increase cafe branding.